Identifikasi Siklus Sipariama Dalam Lontara Pananrang Suku Bugis Terhadap Pengaruh Iklim (Korelasi Peredaran Bulan) - Ahmad Izzuddin; Rahma, Rahmasyarita. S (Universitas Islam Negeri Mataram, 2023)
Based on the Sipariama cycle described in the Lontara Pananrang, we aim to determine a reasonable timing schedule for farming activities in this study. The Buginese people utilise this as a rule of thumb because they believe that the same occurrences occur every eight years and by observing natural signals, they may be certain in their forecasts for this auspicious period. In addition, since the Sipariama cycle's calendar system is based on the Hijri month, which employs the lunar calendar system, this research also attempts to establish a link between the moon's motion and the occurrence of climate change. By comparing the findings of the analysis in the sipariama cycle with the findings of the analysis of the data that had been obtained, the data listed in this paper were taken from the results of analysis from journals related to Lontara Pananrang. According to the findings of this study's work, the Sipariama cycle, which lasted for eight years, solely had a numerical basis. then climatic change, namely the occurrence of air tides, is influenced by the motion of the moon.